Educational Motivation from the Perspective of the Qur’an and Tarbawi Hadiths - Nisa Ayanti; Rahendra Maya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Knowledge and motivation are the main pillars of educational success; within the context of Islamic education, learning motivation contributes not only to academic achievement but also to the formation of faith and moral character. This article explores the concept of educational motivation as presented in the Qur’an and the Prophet’s hadiths, and its implications for modern educational practice. The research method is library research and textual analysis of classical and contemporary sources concerning Qur’anic verses (QS. Al-‘Alaq, Al-Mujadalah, At-Taubah, Az-Zumar) and hadiths related to the virtue of knowledge, the obligation to seek knowledge, and tafaqquh fiddin (deep understanding of religion). Findings indicate that Islamic sources provide a strong normative foundation for learning motivation that encompasses spiritual, moral, social, and cognitive dimensions; recommended motivational strategies include instilling the values of tawhid, teacher role-modeling, use of inspirational narratives, targhib wa tarhib (encouragement and warning), and integration of literacy and research into learning. Contemporary implementation is recommended through integration of faith and knowledge in the curriculum, strengthening literacy and research culture, development of higher-order thinking skills (HOTS), inclusive educational services, and prudent use of digital technology to foster students’ intrinsic and extrinsic motivation. This study affirms that a pedagogical approach that combines normative-religious elements with modern educational practices can address the crisis of motivation in learning and shape a knowledgeable and virtuous generation.